ANALISIS POTENSI KARBON PADA HUTAN MANGROVE DI PESISIR KAWASAN MASJID AL ALAM TELUK KENDARI - ikra safitri; RahmaH Dzulhajjah; Musrim Munazar; Elsa Damayanti; Supriatna supriatna (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2023)
This study aims to determine the morphological basis of carbon storage in mangrove plants, to find out how much carbon storage is according to mangrove vegetation types, and to find out how much total carbon is stored in the Al Alam Mosque Coastal Mangrove Forest Area, Kendari Bay. Data analysis using the approach of determining mangrove tree biomass is calculated using the allometric equation of mangrove trees. The results of this study indicate that the population of mangrove plants as a carbon storage area is spread in the morphology of the roots, stems and leaves under study, namely the stems. The average amount of biomass is 21,100 tons/ha and the average stored carbon gain is 8.96 tons/ha, the type that stores the most carbon is Sonneratia alba with 26.90 tons/ha Biomass and 11.51 tons/ha Carbon and Rhizophora species mucronata Biomass is 20.37 tons/ha and Carbon is 8.96 tons/ha while the least biomass is Bruguiera gymnorhiza with biomass 14.54 tons/ha and carbon 6.40 tons/ha. There are 3 types of mangroves, namely (Sonneratia alba), (Rhizophora mucronata), (Bruguiera gymnorhiza). The total research area is 19.41 ha with a carbon storage gain of 511.1 tons.